Is Sacro-femoral-pubic Angle a Good Indicator of Pelvic Tilt?. Issue 1 (April 2016) - You, Jee Young; Le, Phuong; Cho, Woojin
Introduction: The spino-pelvic alignment is increasingly recognized as crucial in the assessment of patients with spinal deformities. Three pelvic parameters originally described include pelvic incidence (PI), pelvic tilt (PT) and sacral slope (SS). PT, a positional parameter, has been demonstrated to correlate with quality of life and clinical outcomes. Although measuring the PT on sagittal radiographs is simple, underexposed films and malposition of X-rays often result in poor visibility of the femoral heads. In 2012, a novel measurement, the sacro-femoral-pubic (SFP) angle was introduced to estimate the PT using coronal films. The formula PT = 75 – (SFP angle) was derived to correlate the two parameters. Subsequently, the formula was validated in predicting the pelvic tilt in patients with lumbar and thoracic scoliosis. However, more recently another study showed that the SFP angle correlated poorly with the PT. The objective of our study was to analyze whether a correlation exists between the SFP angle and PT in our patient population and to validate the conventional formula (PT = 75 – (SFP angle). We also aimed to identify factors that may contribute to the formula if our data sample fails to validate the formula. Materials and Methods: A retrospective chart review was performed on 106 adult patients who visited an orthopedic spine surgeon of a university hospital. Entire spine posteranterior and lateral spine radiographs were used to measure the PT and SFP, and correlation between PT and SFP was calculated. The validity of the conventional Eq. (75 - SFP =PT) was also tested. In addition, clinical data including age, body mass index (BMI), and gender and other radiographic data including PI, sagittal balance, and presence of scoliosis were analyzed to see if there was any influence of those on using the formula. Results: The conventional Eq. (75 - SFP =PT) did not fit our data. However, the regression model to correlate PT and SFP angle yielded the following formula: PT = 62 – 0.72*SFP (R-square = 0.36). The higher the PI, the greater the tendency of the conventional formula to underestimate the PT and with a lower PI, the conventional formula tended to overestimate the PT (R = −0.38, p  < 0.001). Age, BMI, and gender and sagittal balance did not determine significantly whether the conventional formula worked or not. The conventional formula worked poorer on the patients with scoliosis than patients without scoliosis. Conclusion: The conventional Eq. 75 - SFP =PT did not match our data. However, SFP angle may correlate with PT, but possibly by a nonlinear formula which indicates that there might be additional factors that can contribute to creating such formula such as PI. In reality, however, like PT, PI is obtained from lateral view X-rays. Therefore, a lateral X-ray image with good visibility of the femoral heads would be the best way to measure the PT.